Personal Perceptions of Filariasis of Patients at Kodi Bolaghar Subdistrict, Southwest Sumba Regency, East Nusa Tenggara, Indonesia - Ora, Anderias Parawatu; Irfan, Irfan; Landi, Soleman (Universitas Islam Bandung, 2023)
Perception is a mental process that occurs in humans that will show how we see, hear, feel, give, and feel around us. Patients' positive and negative self-perceptions are internal factors that significantly affect the healing process. Chronic filariasis patients experience a decline in physical condition, which becomes a mental burden for the patients and their families. Patients may experience negative stigma from their family and surrounding community. Some communities still believe in myths, supernatural powers, and magic, and patients suffer illness due to their evil deeds or that they have violated cultural norms that were passed down from generation to generation. How patients perceive themselves, their environment, and their families are rarely studied, though this information is essential to elucidate their needs. Kodi Balaghar subdistrict in the Southwest Sumba regency, East Nusa Tenggara, still has many filariasis cases. This study aimed to know the self-perception of filariasis patients in the Kodi Balaghar subdistrict, Southwest Sumba regency. We have selected ten patients to collect answers regarding self-perception from March to May 2021. The results of our study showed that respondents perceive themselves more negatively to both themselves and their families. We conclude that emotional and spiritual support from family, community, religious leaders, and medical personnel are critical to building self-confidence, life expectancy, enthusiasm, and fighting power to survive and undergo treatment for the disease.